Construction of Chiral Tri‐ and Tetra‐Arylmethanes Bearing Quaternary Carbon Centers: Copper‐Catalyzed Enantioselective Propargylation of Indoles with Propargylic Esters. Issue 33 (27th June 2016) - Tsuchida, Kouhei; Senda, Yasushi; Nakajima, Kazunari; Nishibayashi, Yoshiaki
Abstract: Copper‐catalyzed enantioselective propargylation of indoles with propargylic esters and sequential Huisgen cycloaddition with azides lead to the construction of chiral triarylmethanes, bearing a quaternary carbon center, with high to excellent enantioselectivities. The result described herein can be used in the enantioselective preparation of a tetraarylmethane. Abstract : All‐star all‐carbon : The title reaction leads to the enantioselective construction of an all‐carbon quaternary stereocenter. The subsequent derivatization of terminal alkyne moiety, into aromatic rings, is useful for the construction of chiral all‐carbon substituted tri‐ and tetra‐arylmethanes. The one‐pot procedure demonstrated herein provides a successful example of the enantioselective preparation of a tetraarylmethane.